Sinonasal Schwannoma and Progressive Nasal Obstruction - Fakhriani, Rizka; Herdini, Camelia; Yudistira, Danu (http://dharmais.co.id/, 2024)
Introduction: Schwannomas, are non-malignant tumors with well-defined encapsulation and gradual growth patterns. These tumors consist of Schwann cells, which originate from the neural crest. The prevalence of schwannoma cases in the head and neck region ranges from approximately 25% to 45%. However, in the sinus cavity, the occurrence is only 4%. Case Presentation: In this study, we provide a clinical case with a 25-year-old female patient with rhinorrhoea symptoms, recurrent epistaxis, and a decreased sense of smell. The patient had a progressive obstruction in the right nasal cavity over one year. A biopsy and computed tomography (CT) scan identified a schwannoma and soft tissue density lesions in the right maxillary ethmoid sinuses and left septal deviation. The confirmation of schwannoma diagnosis is also achieved through histopathological examination. The tumor was surgically excised from the patient's body utilizing lateral rhinotomy and an extirpation technique under general anesthesia. The patient had positive outcomes during the follow-up; the patient revealed the absence of symptoms and no evidence of disease recurrence. Conclusions: Lateral rhinotomy with extirpation methods represents an effective option for managing sinonasal schwannoma due to its ability to access challenging anatomical regions and facilitate the sensitive excision of tumors.